Kepentingan Jerman Melalui Program FORCLIME Dalam Penanganan Deforestasi di Kalimantan (2010-2016) - Putra, Tommy Joko; Sushanti, Sukma; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to analyzeGerman’s national interests in Kalimantan Forest by FORCLIME in 2010-2016. Germany as an Annex I country has an obligation to reduce emissions resulting from its industrial activities. REDD+ mechanism allows Germany to reduce its emissions by cooperating with other countries and also maintaining its economic stability resulting from domestic industrial activities. In 2009, Germany reached an agreement with Indonesia of REDD+ implementation by FORCLIME in Kalimantan Forest, which had the highest deforestation rate compared to other forests in Indonesia. FORCLIME has an impact on changing the policies of forest management in Kalimantan. The Regional Government of Kalimantan no longer has full authority over forest management after the establishment of a Forest Management Unit (KPH). Keywords:REDD+, FORCLIME, Germany’s interests in Kalimantan Forest